2018
DOI: 10.1097/md.0000000000010822
|View full text |Cite
|
Sign up to set email alerts
|

Are left ventricular ejection fraction and left atrial diameter related to atrial fibrillation recurrence after catheter ablation?

Abstract: Atrial fibrillation (AF), the most common form of arrhythmia, is associated with the prevalence of many common cardiovascular and cerebrovascular diseases. Catheter ablation is considered the first-line therapy for AF; however, AF recurrence is very common after catheter ablation. Studies have been performed to analyze the factors associated with AF recurrence, but none have reached a consistent conclusion on whether left ventricular ejection fraction (LVEF) and left atrial diameter (LA diameter) affect AF rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…However, age and related comorbidities are sufficient but not necessary to modify the atrial substrate in every patient within a short follow‐up period. However, such an arrhythmogenic mechanism could be predicted and revealed by LA size and AF type . This pathogenic mechanism explains why our study resulted in a nonsignificant difference in the rate of freedom from AF under the condition of different baseline characteristics, except for similar LA diameters and proportions of persAF.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, age and related comorbidities are sufficient but not necessary to modify the atrial substrate in every patient within a short follow‐up period. However, such an arrhythmogenic mechanism could be predicted and revealed by LA size and AF type . This pathogenic mechanism explains why our study resulted in a nonsignificant difference in the rate of freedom from AF under the condition of different baseline characteristics, except for similar LA diameters and proportions of persAF.…”
Section: Discussionmentioning
confidence: 65%
“…Evidence also shows that advanced age (>60 years for the an arrhythmogenic mechanism could be predicted and revealed by LA size and AF type. 21,25 This pathogenic mechanism explains why our study As an evaluation of safety, both the peri-and post-procedural complication rates were comparable between the cohorts. Notably, the stroke (both ischemic and hemorrhagic) and major hemorrhagic event rates were similar in both cohorts.…”
Section: Discussionmentioning
confidence: 68%
“…Arguments favouring a staged approach are avoiding the logistic challenge of facilitating a single-procedure approach and the possibility of temporary (but not long-lasting) conduction block due to tissue oedema or inflammation. 25,66 The relevance of the latter argument, however, seems to be limited, since we found no difference in outcome between single and staged hybrid procedures. While overall success rates were higher after a hybrid procedure, Edgerton et al reported remarkably low success rates (20.8%).…”
Section: Primary Outcomementioning
confidence: 70%
“…Left atrial size was found to be a major determinant for recurrence of AF in different studies. 65,66 The duration and type of AF also negatively influence ablation outcomes. 65,67 Other predictors for failure are older age at time of ablation, female sex, higher CHA 2 DS 2 -VASc scores, obesity, obstructive sleep apnoea and chronic obstructive pulmonary disease.…”
Section: Discussion 165mentioning
confidence: 99%
See 1 more Smart Citation